Social Media and Political Campaign Political Communication Strategies in the 2018 East Java Governor Election - Priyowidodo, Gatut; D. Sari, Yustisia (International Journal of Psychosocial Rehabilitation, 2024)
The regional election has been carried out simultaneously throughout Indonesia in June 2018. Candidates were competing to draw public attention and sympathy by employing communication via social media. Through social media, candidates can share information on their visions, missions, and major programs. The study is aimed at identifying the political strategies and campaign model employed by the social media campaign team of Syaifullah Yusuf (Gus Ipul)-Puti Guntur Soekarno Putri in the 2018 Governor Election. The study was conducted using the netnography method in a qualitative/quantitative paradigm. Data collection was carried out through observation of interactive communication on social media, in-depth interviews, and a literature review. The analysis was conducted using thematic analysis in accordance with the steps in netnography analysis, i.e., by using NVIVO software as the qualitative analysis instrument. The objective of the study was to identify the strategies employed during the campaign for Gus Ipul-Puti Guntur Soekarno Putri. In addition to the open campaign and door-to-door campaign to social communities of smaller sizes, the candidate’s team also campaigned via social media (Facebook, Instagram, YouTube, and Twitter). The model of campaign employed was an in-person campaign and via social media networks. The campaign also included a conventional model, i.e., employing the primary components contained in the delivery and receipt of campaign messages. The campaign model describes that the source (campaign maker) holds a dominant role. He/she is to build messages aimed at creating changes in the targeted audiences (campaign recipients).